THE USE OF DIGITAL EDUCATIONAL RESOURCES IN THE ORGANIZATION OF PRACTICAL CLASSES IN SPECIAL DISCIPLINES BASED ON THE PROJECT METHOD (Scientific journal of the Fergana State University, 2025)
The article discusses the use of digital educational resources in the organization of practical classes in special disciplines in professional educational institutions using the project method. The possibilities of such resources in organizing students' project activities are described.